Circular and Adaptable Building Transformation - Mohammad Basel Hamida (A+BE: Architecture and the Built Environment)
Existing buildings are changing assets, altered in response to various external or internal triggers for change. Often, change can occur in the form of adaptive reuse – also known as building transformation. Therefore, promoting adaptability in transformation is necessary to cope with the inevitability of building changes. Building transformation is considered an effective practice contributing to the circular economy (CE) and building adaptability as a prerequisite for circular design. However, previous research pointed out that building stakeholders lack knowledge about the alignment between CE and adaptive reuse. This study aims to provide building and real estate practitioners with a guiding framework for promoting circularity and adaptability in adaptive reuse projects. A quadrant research design was used in this study to develop and apply the framework in practice. The four components of this research are four stepwise studies, namely theoretical – an integrative literature review, empirical – multiple case studies, participatory – framework co-development, and actionable – framework implementation.